Prevalence of Epilepsy in Dr. Zainoel Abidin Hospital Banda Aceh - Nova Dian Lestari (Universitas Syiah Kuala, 2022)
Background Studies investigating the prevalence and incidence of epilepsy are increasingly common, particularly in low- and middle-income countries. Prevalence is expectedly lowest early in life, increasing to its highest level during adolescence and early adulthood, decreases after age 30, and remains fairly constant for the remainder of life.2 The prevalence of the disease tends to increase with age, with a peak at 20–29 years and a subsequent decrease, with a ratio of 7.17 (95% CI 4.67– 11.01) in individuals aged 60 years or older. Higher rates can be found when the prevalence is calculated in the context of a prospective survey. In the Rotterdam study that included individuals aged 55 years or older, the overall prevalence of active epilepsy was 9 per 1,000, with an increase with age from 7 per 1,000 for people aged 55– 64 years to 12 per 1,000 for those aged 85–94 years. Sex, while not commonly thought to affect the occurrence of epilepsy, may contribute to differences in epilepsy incidence. The incidence of epilepsy tended to be higher in males than females. Some suggest that females may be more likely to conceal their epilepsy diagnosis if they live in a country where they would be considered unmarriageable or socially marginalized.3,4